THE EFFECT OF VOCABULARY MASTERY AND GRAMMAR TO WRITING RECOUNT TEXT SKILLS. (Survey on SMP Negeri in Kabupaten Lebak-Banten) - Yusuf Hekmatiar; Badri; Acep Mulyana Fajrin (Desanta Publisher, 2025)
The purpuse of this study was to : determine the interactive effect of vocabulary mastery and grammar mastery towards recount English writing skill. The research method was used the descriptive survey method. In this study data and the information were collected from respondents using a questionnaire. After the author analyzes the research variables Vocabulary Mastery, Grammar Mastery and Recount Text Writing Ability, it can be concluded that : (1) There are significant interactive effects of vocabulary mastery and grammar mastery trait towards recount English writing ability, as evidenced by the results of Sig = 0,000 < 0,05 and fobserved = 106,807. (2) There is a significant effect of vocabulary mastery towards recount English writing ability, as Sig = 0,000 < 0,05 and tobserved = 7,667 > ttable = 1,663. (3) There is a significant effect of grammar mastery towards recount English writing ability, as Sig = 0,000 < 0,05 and tobserved = 1,615 < ttable = 1,663.